2019
DOI: 10.3390/pr7080523
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue: Modeling and Simulation of Energy Systems

Abstract: This editorial provides a brief overview of the Special Issue "Modeling and Simulation of Energy Systems." This Special Issue contains 21 research articles describing some of the latest advances in energy systems engineering that use modeling and simulation as a key part of the problem-solving methodology. Although the specific computer tools and software chosen for the job are quite variable, the overall objectives are the same-mathematical models of energy systems are used to describe real phenomena and answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Reviews of dynamic simulation applications for optimizing energy and chemical systems are shown in [3,4], while applications of discrete event simulation to the optimization of industrial systems can be found in [4][5][6]. Usage of simulation in specific situations are presented in [7] for sustainable plant design, in [8] for gasifier pressure modeling, and in [9] for analyzing a petrochemical process wastewater plant.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Reviews of dynamic simulation applications for optimizing energy and chemical systems are shown in [3,4], while applications of discrete event simulation to the optimization of industrial systems can be found in [4][5][6]. Usage of simulation in specific situations are presented in [7] for sustainable plant design, in [8] for gasifier pressure modeling, and in [9] for analyzing a petrochemical process wastewater plant.…”
Section: A Literature Reviewmentioning
confidence: 99%